Layered Cuprates Containing Flat Fragments: High-Pressure Synthesis, Crystal Structures and Superconducting Properties - Evgeny M. Kopnin (Molecules, 2021)
High-pressure synthesis and crystal structures of the homologous series AuBa2(Ca,Ln)n−1CunO2n+3 (n = 1–4; Ln = rare-earth cations) are described. Their crystal structures and superconducting properties are compared with the corresponding members of the Hg-homologous series. Numerous cuprates containing flat structural fragments (CuO4, CO3 and BO3) synthesized mainly at high pressure are compared in terms of structural peculiarities and superconducting properties. Importance and future prospects of high-pressure application for the preparation of new superconducting oxides are discussed.